Diagnosis of Deep Infiltrating Endometriosis Using Transvaginal Ultrasonography - Yin, Shaoli; Lin, Qi; Xu, Fanhua; Xu, Jinfeng; Zhang, Yujuan (Frontiers in Medicine, 2020)
Objective: To evaluate the performance of transvaginal ultrasonography (TVS) in diagnosis of deep infiltrating endometriosis (DIE). Methods: We retrospectively analyzed 198 patients with pathological diagnosis of DIE in our hospital from January 2017 to December 2019 and assessed the performances of pre-operative TVS diagnosis of DIE with regarding to sensitivity (SE), specificity (SP), positive predictive value (PPV), and negative predictive value (NPV), using the pathological diagnosis as the ground truth. We also characterized the ultrasonographic features of the DIE lesions. Results: Among all the 198 cases, 170 cases were uterosacral ligament (USL) involvement, SE: 96.47% and SP: 85.71%; 79 cases were intestinal involvement, SE: 94.94% and SP: 94.96%; 57 cases were vaginal rectal septum (VRS) involvement, SE: 73.68% and SP: 94.33%; 20 cases were vaginal involvement, SE: 50% and SP: 97.21%; three cases were bladder involvement, SE: 66.7% and SP: 100%; nine cases were ureter involvement, SE: 55.56% and SP: 100%; and 10 cases were broad ligament involvement, SE: 10% and SP: 100%. Conclusion: TVS showed high accuracy in diagnosing DIE.